PlanktoScope: Affordable Modular Quantitative Imaging Platform for Citizen Oceanography - Pollina, Thibaut; Larson, Adam G.; Lombard, Fabien; Li, Hongquan; Le Guen, David; Colin, Sébastien; de Vargas, Colomban; Prakash, Manu (Frontiers in Marine Science, 2022)
The oceans represent 97% of all water on Earth and contain microscopic, drifting life, plankton, which drives global biogeochemical cycles. A major hurdle in assessing marine plankton is the planetary scale of the oceans and the logistical and economic constraints associated with their sampling. This difficulty is reflected in the limited amount of scientifically equipped fleets and affordable equipment. Here we present a modular hardware/software open-source strategy for building a versatile, re-configurable imaging platform - the PlanktoScope - that can be adapted to a number of applications in aquatic biology and ecology. We demonstrate high-throughput quantitative imaging of laboratory and field plankton samples while enabling rapid device reconfiguration to match the evolving needs of the sampler. The presented versions of PlanktoScope are capable of autonomously imaging 1.7 ml per minute with a 2.8 µm/px resolution and can be controlled from any WiFi-enabled device. The PlanktoScope’s small size, ease of use, and low cost - under 1000 in parts - enable its deployment for customizable monitoring of laboratory cultures or natural micro-plankton communities. This also paves the way toward consistent and long-term measurement of plankton diversity by an international fleet of citizen vessels at the planetary scale.